A comprehensive approach to scenario-based risk management for Arctic waters. Issue 3 (2nd September 2022) - Bergström, Martin; Browne, Thomas; Ehlers, Sören; Helle, Inari; Herrnring, Hauke; Khan, Faisal; Kubiczek, Jan; Kujala, Pentti; Kõrgesaar, Mihkel; Leira, Bernt Johan; Parviainen, Tuuli; Polojärvi, Arttu; et al.
ABSTRACT: While society benefits from Arctic shipping, it is necessary to recognize that ship operations in Arctic waters pose significant risks to people, the environment, and property. To support the management of those risks, this article presents a comprehensive approach addressing both short-term operational risks, as well as risks related to long-term extreme ice loads. For the management of short-term operational risks, an extended version of the Polar Operational Limit Assessment Risk Indexing System (POLARIS) considering the magnitude of the consequences of potential adverse events is proposed. For the management of risks related to long-term extreme ice loads, guidelines are provided for using existing analytical, numerical, and semi-empirical methods. In addition, to support the design of ice class ship structures, the article proposes a novel approach that can be used in the conceptual design phase for the determination of preliminary scantlings for primary hull structural members.